Novice Teachers’ Challenges and Support in their First Years - Mahmudova, Shalala; Jalilova, Khumar; Rustamov, Alekper (ADA University, 2020)
Education as an open and dynamic system receives novice teachers every year. Novice teachers enter public schools in Azerbaijan with certain content and pedagogical knowledge, personal background and expectations. This project explores the challenges that the novice teachers in two public schools in Baku encounter in the first years of their career and the support that those beginning teachers receive. The researchers employed interviewing to identify the form of challenges that the novice teachers face, the sources and form of support that they receive and the support that they would like to receive. The challenges that these teachers confront include issues related to communication with the pupils and their parents, novice teachers’ pedagogical skills and teaching strategies, how these teachers adapt to the profession, documentation challenges technical and teaching resources challenges. The findings of this study highlight that the novice teachers receive support from their experienced colleagues, school administration, Ministry of Education and Baku Education Department. The research shows that novice teachers are very interested in self-improvement; they continuously explore different Internet resources and get advice from other people such as their parents and friends who are related to teaching profession. Novice teachers’ suggestions regarding the support that they would prefer to receive differ and include various professional development programs, helping teacher, collaboration with colleagues at school or in other schools as well as in online platforms, quality and long term internship programs at university and additional guidance and teaching resources. A special mentoring program was suggested depending on the results of the study.
Keywords: Education; Mentoring program.; Education -- Azerbaijan.